The Use of A Scientific Approach to Improve Argumentation Writing Ability for Middle School Students - Wahyuningsih, Lucia Sri; Sutiyono, Akhmad; Hastomo, Tommy (IJLHE: International Journal of Language, Humanities, and Education, 2019)
This study aimed to determine and describe the improvement of argumentation writing skills through a scientific approach to class VIII students of SMP Negeri 18 Bandar Lampung in the 2018/2019 academic year. The method in this study used a classroom action research design carried out in three cycles. This research was conducted in three cycles. The teacher prepares the lesson plan for each cycle. Each action consists of four stages: planning, action, observation, and reflection. The reflection results are used as the basis for developing a further action plan. Therefore, this research can be called collaborative classroom action research. The results showed that the scientific approach could improve the argumentation writing skills of SMP Negeri 18 Bandar Lampung students. Based on the research results in the first cycle, 49% for classical achievement and 28% for the number of students who got the minimum standard score increased in Cycle II, which reached 63% for classical achievement and 69% for students who finished studying. While Cycle III, which is the implementation of the final action, the results show the learning objectives in general and the research objectives in particular, namely reaching 75% for classical achievement and 85% for students' high argumentative writing skills. The scientific approach used in the learning process can improve the ability to write arguments.